2016
DOI: 10.5334/pb.252
|View full text |Cite
|
Sign up to set email alerts
|

The Portuguese Validation of the Basic Psychological Need Satisfaction and Frustration Scale: Concurrent and Longitudinal Relations to Well-being and Ill-being

Abstract: This research comprises two studies based on Self Determination Theory. In Study 1, we translate and examine the factor structure of the Basic Psychological Needs Satisfaction and Frustration Scale (BPNSFS; Chen, Vansteenkiste et al., 2015) in a sample of Portuguese undergraduate students. Further, in Study 2 we used an independent longitudinal sample of 12th grade students to inspect whether the six subscales differently predict adjustment over time. Confirmatory factor analysis showed that a six-factor solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
79
1
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(101 citation statements)
references
References 37 publications
12
79
1
9
Order By: Relevance
“…The BPNSFS is currently the most widely used measure. Originally validated in Dutch, English, Spanish, and Chinese, today a variety of translations and contextspecific adaptations are available, including validations in German (Heissel et al 2018), Japanese (Nishimura and Suzuki 2016), Italian (Costa et al 2018), Hebrew (Benita et al 2020), Turkish (Selvi and Bozo 2020), and Portuguese (Cordeiro et al 2016). It has also been adapted for specific contexts, including work (Rouse et al 2020;Schultz et al 2015), school (Vandenkerckhove 2019b), and volunteering, among others (see Appendix for an overview of different translations and adaptations).…”
Section: Theme 2: Which Costs Are Associated With Basic Psychologicalmentioning
confidence: 99%
See 1 more Smart Citation
“…The BPNSFS is currently the most widely used measure. Originally validated in Dutch, English, Spanish, and Chinese, today a variety of translations and contextspecific adaptations are available, including validations in German (Heissel et al 2018), Japanese (Nishimura and Suzuki 2016), Italian (Costa et al 2018), Hebrew (Benita et al 2020), Turkish (Selvi and Bozo 2020), and Portuguese (Cordeiro et al 2016). It has also been adapted for specific contexts, including work (Rouse et al 2020;Schultz et al 2015), school (Vandenkerckhove 2019b), and volunteering, among others (see Appendix for an overview of different translations and adaptations).…”
Section: Theme 2: Which Costs Are Associated With Basic Psychologicalmentioning
confidence: 99%
“…Need frustration has also been found to be a robust predictor of a variety of ill-being indicators, including stress (Campbell et al 2017; Weinstein and Ryan 2011), depressive symptoms (Cordeiro et al 2016), and anxiety (Ng et al 2012). Such findings are evident at both the level of (relatively stable) between-person differences and at the level of within-person fluctuations across time, with monthly, weekly, daily, and even hourly fluctuations in need frustration co-varying with fluctuations in corresponding negative affect (e.g., Vandenkerckhove et al 2019b), stress (e.g., Howell et al 2011), or depressive symptoms (e.g., Bartholomew et al 2018).…”
Section: Advancementsmentioning
confidence: 99%
“…People throughout the world desire better lives in the pursuit of happiness (Cordeiro, Paixão, Lens, Lacante, & Luyckx, 2016). Accordingly, researchers have increasingly focused on what affects individuals’ life satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…According to Self-Determination Theory (SDT; Deci & Ryan, 2000) psychological control is assumed to thwart adolescents’ needs for autonomy and relatedness and to result in negative affect towards its provider. CNR may be expected to thwart adolescents’ needs in similar ways and, thus, result in enhanced negative effects on self-esteem, affect and motivation following failure (Cordeiro, Paixao, Lens, Lacante, & Luyckx, 2016; Kanat-Maymon et al, 2015; Roth et al, 2009; Wouters et al, 2014). With regard to the effects of CPR, studies have shown retrospective reports of CPR in close relationships to have psychological costs (Assor et al, 2014; Kanat-Maymon et al, 2015).…”
mentioning
confidence: 99%